Space debris in low earth orbits region: Formation and reduction process analysis in past decade. (May 2022) - Nazarenko, A.I.; Usovik, I.V.
Abstract: The paper considers main features of spacecraft launch traffic, break-up events in orbit, re-entry of space objects from low Earth orbits region (altitude up to 2000 km above the Earth's surface) for the period from 2010 to mid-2021. Conclusions are drawn regarding to main regularities of processes of increasing and decreasing the number of space objects in orbit. Statistical models for predicting space debris based on analyzed data have been developed. Highlights: Main features of spacecraft launch traffic, break-up events, re-entry from LEO region for the period from 2010 to mid-2021. Conclusions are drawn regarding main regularities of processes of increasing and decreasing the number of space objects in orbit. Statistical models for predicting space debris based on analyzed data have been developed.